2013
DOI: 10.1016/j.nuclphysb.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Mirror symmetry: from active and sterile neutrino masses to baryonic and dark matter asymmetries

Abstract: We consider an SU (3) ′ c × SU (2) ′ L × U (1) ′ Y mirror sector where the field content and dimensionless couplings are a copy of the SU (3) c × SU (2) L × U (1) Y ordinary sector. Our model also contains three gauge-singlet fermions with heavy Majorana masses and an [SU (2) L × SU (2) ′ L ]-bidoublet Higgs scalar with seesaw-suppressed vacuum expectation value. The mirror sterile neutrino masses will have a form of canonical seesaw while the ordinary active neutrino masses will have a form of double and line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“…Experiments have shown that this is not the case; the solar, atmospheric, and longbaseline neutrino experiments can all be accounted for with just the three ordinary neutrinos (see for example the review [127]). Some anomalies remain, but it seems unlikely that they could be explained with mirror neutrino oscillations, unless the mirror symmetry was broken in some way (see [128] for some recent work in this direction). The conclusion is that on length scales probed by the solar, atmospheric, and longbaseline neutrino experiments, there is no convincing evidence for any oscillations into mirror neutrinos.…”
Section: Type-iii Seesawmentioning
confidence: 99%
“…Experiments have shown that this is not the case; the solar, atmospheric, and longbaseline neutrino experiments can all be accounted for with just the three ordinary neutrinos (see for example the review [127]). Some anomalies remain, but it seems unlikely that they could be explained with mirror neutrino oscillations, unless the mirror symmetry was broken in some way (see [128] for some recent work in this direction). The conclusion is that on length scales probed by the solar, atmospheric, and longbaseline neutrino experiments, there is no convincing evidence for any oscillations into mirror neutrinos.…”
Section: Type-iii Seesawmentioning
confidence: 99%
“…For the first task, we use baryogenesis via leptogenesis resulting from the decay of heavy Majorana 1 While we only consider G being the standard model gauge group in this paper, it is possible to extend the construction to mirror GUT theories; see, for example, Refs. [42,[46][47][48][49][50]. Such models can be further motivated by the E 8 ⊗ E 8 symmetry of the heterotic string model.…”
Section: Introductionmentioning
confidence: 99%
“…[76] a mirror model that relied on explicit breaking in different Yukawa couplings between the sectors was considered. Similar models have considered simply a common set of singlet neutrinos shared between the sectors [77][78][79]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many attempts to solve this problem by introducing the Peccei-Quinn symmetry and axion [2][3][4][5], left-right symmetry [6][7][8][9][10]. These extensions have been discussed with applications to neutrino physics [11], the baryon asymmetry [12,13], the LHC physics [14,15], grand unification [16], flavor physics [17][18][19][20] and DM physics [21,22].…”
Section: Introductionmentioning
confidence: 99%